British Jews and Anti-Fascism in the 1930s. Issue 3 (1st September 2020) - Dee, David
ABSTRACT: Focusing on the experiences and life histories of 35 individuals, this article sheds light on the nature and extent of, and underpinning motivation for, anti-Fascism - both in the UK and during the Spanish Civil War - undertaken by persons of British Jewish heritage during the 1930s.It demonstrates and explores the development of two main, existing, frameworks of understanding regarding such actions (i.e. that it was purely politically driven/motivated by Jewish 'ethnic reactions'), but also introduces the sociological concept of 'reactive ethnicity' to point towards a third, new, explanation for British Jewry's contemporary anti-Fascist tradition.